2005
DOI: 10.1152/ajpregu.00403.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia-induced noradrenergic activation in the VMH is a result of decreased ambient glucose

Abstract: During insulin-induced hypoglycemia, there is an increase in extracellular norepinephrine (NE) in the ventromedial hypothalamus (VMH). This brain area is known to play an important role in integrated hormonal and behavioral responses to systemic hypoglycemia. Selective glucoprivation restricted to the VMH is both necessary and sufficient to initiate secretion of counterregulatory hormones. The present study was designed to investigate whether increased release of NE in the VMH depends on detection of glucopriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 33 publications
3
39
0
Order By: Relevance
“…While one study has shown that the source of norepinephrine in humans is primarily adrenomedullary (9), data from animal models suggest that central regulation of sympathetic output may be more complicated and organ specific (21). For example, increased levels of norepinephrine have been found within the brain during hypoglycemia, specifically in the paraventricular (11,26) and ventromedial nuclei (10), and despite reduced systemic levels, these hypothalamic levels were not reduced after multiple daily episodes of hypoglycemia (11). These authors postulated that the mechanism for blunted sympathoadrenal responses with repeated hypoglycemia occurs downstream from the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While one study has shown that the source of norepinephrine in humans is primarily adrenomedullary (9), data from animal models suggest that central regulation of sympathetic output may be more complicated and organ specific (21). For example, increased levels of norepinephrine have been found within the brain during hypoglycemia, specifically in the paraventricular (11,26) and ventromedial nuclei (10), and despite reduced systemic levels, these hypothalamic levels were not reduced after multiple daily episodes of hypoglycemia (11). These authors postulated that the mechanism for blunted sympathoadrenal responses with repeated hypoglycemia occurs downstream from the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Am J Physiol Endocrinol Metab 293: E1511-E1516, 2007. First published October 16, 2007; doi: 10.1152/ajpendo.00340.2007.-The aim of this study was to test the hypothesis that antecedent short-term administration of estradiol or progesterone into the central nervous system (CNS) reduces levels of neuroendocrine counterregulatory hormones during subsequent hypoglycemia. Conscious unrestrained male Sprague-Dawley rats were studied during randomized 2-day experiments.…”
mentioning
confidence: 99%
“…Blood glucose levels in rats are typically around 5-6 mM (de Vries et al, 2003(de Vries et al, , 2005. However, in anesthetized animals these levels are reported to increase 2-fold (Moon et al, 2013).…”
Section: Basal Glucose Levelsmentioning
confidence: 99%
“…The concentration of extracellular glucose in the VMH is 20 -25% of plasma glucose under euglycemic conditions and generally declines in parallel with plasma glucose during hypoglycemia (8). When VMH glucose was maintained during systemic hypoglycemia, peripheral sympathoadrenal responses were attenuated (3,10), demonstrating that the reduction of glucose within the VMH is both required and sufficient for activation of CRR. Activation of noradrenergic systems in the VMH increased sympathetic nervous system activity, a mediator of glucose mobilization (31), and there is an increase in NE release in the VMH during hypoglycemia (2) that occurs in response to the decrease in VMH glucose (10).…”
mentioning
confidence: 99%